PENINGKATAN HASIL BELAJAR MATEMATIKA DALAM KEGIATAN BIMBINGAN BELAJAR BERHITUNG PADA TINGKAT ANAK SEKOLAH DASAR DI KELURAHAN PANCURAN PINANG KOTA SIBOLGA - Sormin, Masdelima Azizah; Sakinah, Wafiahtus; Nurhasanah, Nurhasanah; Pardede, Janna Khairani (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
The aims of the research are: 1) the beginning of mathematics for elementary school children before tutoring is held, 2) Implementation of tutoring in Pancuran Pinang Village, Sibolga City, 3) Mathematics Learning Results for elementary school children after tutoring for arithmetic is carried out. Classroom Action Research (PTK) with 20 elementary school children as subjects. The object of the research is improving mathematics learning outcomes for elementary level children in numeracy tutoring activities. In this case, the data collection technique used is essay questions and documentation in the form of photos. The data analysis technique is quantitative. Based on calculations after carrying out tutoring for elementary level students in Pancuran Pinang Village, Sibolga City, the results of children's mathematics learning tests were obtained. After giving the test to 20 people at the end of the meeting, cycle I obtained an average score of 70.64 or a percentage of 70.64% and as many as 12 people. Continuing in cycle 2, the results were 80%, namely 87.20% and as many as 19 students. So the increase in children's mathematics learning test results was 16.56%.